{Heat shock protein beta 3 (HSPB3) is an unfavorable molecular biomarker in colorectal adenocarcinoma} - Kalioraki, Maria Anna; Artemaki, Pinelopi I.; Sklirou, Aimilia D.; Christos K. Kontos; Adamopoulos, Panagiotis G.; Iordanis N. Papadopoulos; Trougakos, Ioannis P.; Andreas Scorilas (Molecular Carcinogenesis, 2020)
Small heat shock proteins (sHSPs) participate in numerous cellular functions including cell signaling, differentiation, and apoptosis. Deregulation of the physiological expression level of sHSPs has been associated with several malignancies. Heat shock protein beta 3 (HSPB3) is the third member of the sHSP family in human and is mainly expressed in skeletal and smooth muscles. In this study, we investigated the potential prognostic significance of HSPB3 expression in colorectal adenocarcinoma, the most frequent type of colorectal cancer. For this purpose, we isolated total RNA from 188 colorectal adenocarcinoma specimens and 68 paired noncancerous ones. After reverse transcription of 2 $μ$g total RNA, we quantified HSPB3 levels by using an in-house–developed real-time quantitative polymerase chain reaction method, based on the SYBR Green chemistry. Comparison of HSPB3 levels among 68 pairs of colorectal tumors and their adjacent noncancerous mucosae uncovered the downregulation of HSPB3 expression in the majority of malignant colorectal tumors. More importantly, high HSPB3 expression is associated with poor relapse-free survival (RFS) and overall survival (OS) of patients with colorectal adenocarcinoma. Multivariable Cox regression analysis revealed that HSPB3 overexpression could serve as an adverse prognostic biomarker in colorectal adenocarcinoma, independent of tumor location, histological grade, and TNM stage. Patients' stratification according to tumor location, histological grade, and TNM stage revealed that high HSPB3 messenger RNA expression retains its unfavorable prognostic potential regarding OS, in particular groups of patients with substantially different prognosis. In conclusion, high HSPB3 expression is associated with poor RFS and OS of patients with colorectal adenocarcioma, independently of clinicopathological prognosticators.
Keywords: Colorectal cancer; HSPB3; molecular tumor markers; Prognosis; prognostic biomarkers